1984
DOI: 10.1136/bmj.288.6430.1567
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pneumococcal infection in children with homozygous sickle cell disease.

Abstract: The efficacy of prophylactic penicillin and of 14 valent pneumococcal vaccine in preventing pneumococcal infection in homozygous sickle cell (SS) disease was investigated in 242 children aged 6 months to 3 years at entry. In the first five years of the trial there were 11 pneumococcal infections in the pneumococcal vaccine treated group, 10 by serotypes present in the vaccine. Type 23 accounted for five of these, and there was evidence of higher infection rates in those given the vaccine before age 1. No pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
3

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(90 citation statements)
references
References 15 publications
3
84
0
3
Order By: Relevance
“…The widespread use of prophylactic penicillin and the ready availability of antibiotics in the home may have precluded culture and latex slide agglutination documentation of some incidence of bacterial infection during the last few years. We find little data to support the use of prophylactic penicillin (or other antibiotic) regimens in previously untreated but immunized American SS patients greater than 3 years of age who have ported that children over 3 years of age had pneumococcal infections upon stopping penicillin prophylaxis [24]. This issue is currently under investigation in Phase I1 American trials.…”
Section: Resultsmentioning
confidence: 95%
“…The widespread use of prophylactic penicillin and the ready availability of antibiotics in the home may have precluded culture and latex slide agglutination documentation of some incidence of bacterial infection during the last few years. We find little data to support the use of prophylactic penicillin (or other antibiotic) regimens in previously untreated but immunized American SS patients greater than 3 years of age who have ported that children over 3 years of age had pneumococcal infections upon stopping penicillin prophylaxis [24]. This issue is currently under investigation in Phase I1 American trials.…”
Section: Resultsmentioning
confidence: 95%
“…A single center trial [33], followed by a multicenter, randomized clinical trial unequivocally demonstrated the benefit of penicillin prophylaxis for preventing SCD related pneumococcal sepsis. In the "PRophylaxis with Oral Penicillin in children with Sickle cell anemia" (PROPS) trial, children with SCA younger than 3 years were randomly assigned to receive either 125 mg of penicillin V (105 children) or placebo (110 children) twice daily [34].…”
Section: Milestones In Scd Carementioning
confidence: 99%
“…The results of the trial by John (2) show that prophylactic penicillin is feasible in resource-limited countries. The cost is low (approximately US$1 per month) and monthly injections may aid compliance, providing individuals attend clinics regularly.…”
Section: Prophylactic Antibiotics For Preventing Pneumococcal Infectimentioning
confidence: 94%